2011
DOI: 10.1007/978-3-642-21934-4_37
|View full text |Cite
|
Sign up to set email alerts
|

Two-Directional Two-Dimensional Random Projection and Its Variations for Face and Palmprint Recognition

Abstract: Abstract. 2DRP (two-dimensional random projection) is two-dimensional extension of one-dimensional RP (random projection) to keep biometric images from being reshaped to vectors before RP for recognition. We propose a novel method called (2D) 2 RP (two-directional two-dimensional random projection) for feature extraction of biometrics. (2D) 2 RP directly projects the image matrix from high-dimensional space to low-dimensional space to extract optimal projective vectors at row-direction and column-direction. (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…This interest is somehow shared almost at the same time by A. Eftekhari et al [32] and L. Leng et al [33]. Although addressing the same problem, the focuses of A. Eftekhari, L. Leng et al [32,33] and ours are different.…”
Section: Contributions Of This Studymentioning
confidence: 67%
See 4 more Smart Citations
“…This interest is somehow shared almost at the same time by A. Eftekhari et al [32] and L. Leng et al [33]. Although addressing the same problem, the focuses of A. Eftekhari, L. Leng et al [32,33] and ours are different.…”
Section: Contributions Of This Studymentioning
confidence: 67%
“…Although addressing the same problem, the focuses of A. Eftekhari, L. Leng et al [32,33] and ours are different. Besides the theoretical analysis of 2D random projection and the assumption that 2D signal is sparse, A. Eftekhari et al reported a reconstruction algorithm of 2D sparse signal based on smoothed 0 -norm minimization.…”
Section: Contributions Of This Studymentioning
confidence: 90%
See 3 more Smart Citations